Universal domino reaction strategy for mass production of single-atom metal-nitrogen catalysts for boosting CO2 electroreduction. (April 2021) - Wang, Xingpu; Ding, Shaosong; Yue, Tong; Zhu, Ying; Fang, Mingwei; Li, Xueyan; Xiao, Guozheng; Zhu, Ying; Dai, Liming
Abstract: Developing efficient electrocatalysts for CO2 conversion into value-added chemicals is highly desirable, but it still remains a great challenge to achieve scalable production of these catalysts that displays simultaneously the high product selectivity and large current density at a low overpotential. Here, we develop a universal domino reaction strategy for mass production of metal single atoms anchored on N-doped carbon nanosheets (M-SA/NC), including Fe, Co, Ni, Mn, Mo, Pd and combinations thereof (among FeCo, FeNi, FeCoNi) SA/NC by ball-milling of polyaniline (PANI) with appropriate salts (e.g., NiCl2, NaCl and NaNO3 ), followed by pyrolysis. During pyrolysis, NaNO3 is decomposed in-situ to release gases capable of blowing PANI, then carbon sheets from carbonized PANI is etched by O2 to create microporous and the aggregated metal particles is etch by CO. The as-prepared Ni-SA/NC exhibits an extraordinary catalytic activity for CO2 reduction to CO, yielding a large current density of 213.2 mA cm −2 with CO Faradaic efficiency up to 96.9% at a low overpotential of 0.55 V in a flow cell. DFT calculations reveal that N atoms in NiN4 species act as the active sites for CO2 RR, rather than conventional Ni atoms, since the neighboring pyrrolic-N induces electrons of Ni 4s orbitals shift to adjacent N 2s orbitals in NiN4, leading to a high N 2s electron density for facilitating the COOH* formation. This work provides not only a rational design concept for mass preparation of M-SA/NC heterogeneous electrocatalyst for CO2 reduction and beyond, but also a deep insight of an electron transfer mechanism for CO2 RR. Graphical Abstract: We developed a domino reaction strategy for mass production of efficient M-SA/NC catalysts, as exemplified by an excellent electrocatalytic activity of Ni-SA/NC for the conversion of CO2 to CO. Neighboring pyrrolic-N induces the electron transfer from Ni 4s orbitals to adjacent N4 2s orbitals in NiN4 to significantly enhance electroreduction of CO2 . ga1 Highlights: A universal domino reaction strategy for mass production of M-SA/NC catalysts. Ni-SA/NC exhibited excellent catalytic performance for CO2 RR. Pyrrolic-N adjacent to NiN4 sites induced the shift of Ni 4s electrons to N 2s orbital in NiN4 for boosting the CO2 electroreduction.